Rh Doping in Pd Nanocubes Optimizes the Adsorption of 3‐Nitrostyrene towards Selective Hydrogenation of Vinyl Group. Issue 12 (15th May 2019) - Wu, Wenlong; Zhao, Songtao; Cui, Yi Eason; Chen, Wenze; Liu, Yulin; Wang, Haoyuan; Li, Jiawei; Li, Zhenyu; Zeng, Jie
Abstract: For selective hydrogenation, the improvement in selectivity is often accompanied with the sacrifice of activity. Herein, we achieved the optimization of both activity and selectivity towards selective hydrogenation reaction of 3‐nitrostyrene over Rh‐doped Pd nanocubes. Specially, the Rh‐doped Pd nanocubes with 6 atm % of Rh (denoted as Pd94 Rh6 ) achieved a remarkable high selectivity (99.5 %) for product 3‐ethylnitrobenzene with almost 100 % conversion. Mechanistic studies revealed that the introduction of Rh dopant into Pd nanocubes strengthened the adsorption of 3‐nitrostyrene relative Pd nanocubes, accounting for the enhanced activity. Moreover, the ensemble composed of Rh dopant and nearby Pd atoms in Rh‐doped Pd nanocubes induced the unique adsorption configuration of 3‐nitroethylbenzene that inhibited the hydrogenation of NO2, responsible for the high C=C selectivity. Abstract : Hydrogenation of 3‐nitrostyrene over Rh‐doped Pd nanocubes : The introduction of Rh into Pd nanocubes enhanced both the activity and selectivity for C=C in the presence of NO2 group due to the strengthened adsorption of 3‐nitrostyrene and unique configuration of 3‐nitroethylbenzene.